Elucidation of Abiotic Stress Signaling in Plants 2015
DOI: 10.1007/978-1-4939-2540-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Mechanisms of Flooding Tolerance in Plants

Abstract: Flooding is a crucial factor affecting crop growth and yield in low-lying rainfed areas. Systematic investigation of fl ooding survival mechanisms in tolerant species has deciphered molecular, physiological, and developmental basis of soil fl ooding (waterlogging) and submergence survival. Flood escape and quiescence strategies of deepwater and submergence-tolerant rice ( Oryza sativa ) plants are regulated by ethylene-responsive factor (ERF) transcriptional activators. Ethylene induces genes of enzymes associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Most plants need to respond to hypoxic stress at various points in their lifecycles. Mostly obviously, heavy rain or flooding will result in soil water logging will limit the ability of oxygen to diffuse to the roots [28]. Plants may employ one of many physiological responses to submergence including hyponasty, elongation of floral stems, petioles or internodes or even the formation of aerial roots [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most plants need to respond to hypoxic stress at various points in their lifecycles. Mostly obviously, heavy rain or flooding will result in soil water logging will limit the ability of oxygen to diffuse to the roots [28]. Plants may employ one of many physiological responses to submergence including hyponasty, elongation of floral stems, petioles or internodes or even the formation of aerial roots [29].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, higher carbohydrate consumption in hypoxic roots (Lekshmy et al. ) may impede carbohydrate investment and morphological adjustments in leaves, reversing the positive effects of shade.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reduced incident light may reduce the negative effects of waterlogging on cotton by increasing leaf expansion (Mommer et al 2005). Alternatively, higher carbohydrate consumption in hypoxic roots (Lekshmy et al 2015) may impede carbohydrate investment and morphological adjustments in leaves, reversing the positive effects of shade.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is a high susceptibility of cultivated plants to waterlogging stress, affecting their growth, development, yield, and finally their survival [9,10]. One of the main effects of waterlogging is on plant growth.…”
Section: Introductionmentioning
confidence: 99%